Internalisasi Nilai-Nilai Pendidikan Agama Islam melalui Pembelajaran Al-Qur’an pada Anak Usia Dini - Ulfa, Ulfa (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2017)
Early childhood they are in the golden age, because at this time, child is like a white paper thatis not stained, Parents and teachers who are responsible for giving them a good life color. Islamis a religion whose teachings are perfect, it will not be lost in the child's life if they are givenknowledge about Islamic religious education. So it is very easy to provide Islamic religiouseducation, In this case through learning the Qur'an, because in learning the Qur'an there arevarious materials given to the child either that way of reading the Qur'an is good and correctalso learning about the content of the content contained in the Qur'an. the internalization of thevalue of Islamic religious education is very easy to be accepted by the early childhood, in thehope that in the future they can become good Muslims, who are obedient to their religion, sothat he achieves happiness in the world and in the afterlife.